Meningkatan Kesadaran Berwirausaha Kepada Kalangan Muda Di Kota Banjarmasin Melalui Kegiatan Sosialisasi Kewirausahaan - Kurniawan, Eki; Muhammad Ilham; Reza Aurea Rabbanie; Chris Kelvin Timothi; Hendra Kustiono; Sudirwo; Anna Nur Faidah (Journal Of Rural Community Development, 2025)
This community service program was carried out to enhance entrepreneurial awareness and interest among young people in Banjarmasin. An initial situation analysis indicated that most youth prefer becoming employees rather than developing their own businesses, which limits economic independence and the emergence of new entrepreneurs. The main problems identified include low understanding of entrepreneurship concepts, limited access to mentoring, and common challenges such as lack of capital and business experience. The program was implemented through educational sessions, interactive discussions, and practical mentoring, covering entrepreneurial mindset development, creative and innovative thinking, business planning, digital marketing strategies, and simple yet effective financial management. The results showed an improvement in participants’ knowledge regarding the steps to start a business and strategies to overcome early-stage entrepreneurial challenges. Participants also demonstrated stronger motivation to explore business ideas based on local potentials. Overall, this program contributes to strengthening youth entrepreneurial capacity and is expected to encourage their role in supporting local economic growth in Banjarmasin.